Studi Analitik Nilai-Nilai Pendidikan dalam Al-Qur'an Surah Al-'Ankabut Ayat 16-25 dalam Pandangan Ibnu Katsir - Wahyudi, Muhammad; Hamdan Syukri (TAUJIH: Jurnal Pendidikan Islam, 2024)
The Qur'an is the word of Allah SWT which was revealed gradually (mutawatir) to the Prophet Muhammad SAW through the angel Gabriel and reading it is worship. In addition, the Qur'an also as "hudan” (guidance) for humans so that humans can be guided in carrying out their duties as caliphs on earth. The Qur'an is not just a religious symbol but contains values that are useful for life, including education that guides humans to become civilized and moral people, whoever follows the guidance of the Qur'an, namely studying, understanding and practicing the values of the Qur'an. -Qur'an then Allah SWT promises safety and happiness in this world and in the afterlife. Among these values are found in the Al-Qur'an Surah Al-‘Ankabut verses 16 to 25. This research is a qualitative type of research library research. Library research is collecting data by studying and understanding data that is closely related to problems from books, theories, notes and documents. The data analysis technique uses the content analysis method, which is a method for drawing conclusions after making systematic and objective efforts to identify message characteristics. The results of this research show that the educational values in the Al-Qur'an Surah Al-‘Ankabut verses 16-25, namely First; the value of faith education, second; the value of religious education, third; the value of moral education, and fourth; the value of historical education.